ANALISIS PENGGUNAAN BAHASA IBU DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: Bahasa Indonesia - Saputri, Novita Zulfa (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
The first language a child masters when learning to speak is the mother tongue. Mother tongues also vary, after mastering the mother tongue of course with various demands and motivations a person learns a second language, a third language based on their needs. The research method uses qualitative with interactive analysis techniques. The purpose of this writing is to describe the use of the mother tongue in learning Indonesian in elementary schools. The position of the Indonesian language as an introduction to learning is normal and indeed mandatory. However, the use of regional language-based mother tongue is really rare, especially in learning in formal schools. However, this learning is felt to be effective enough to be applied in efforts to preserve regional languages which are almost left out by the large number of parents who teach their first language using the national language. It's ironic like a frightening specter. All of this can be avoided by implementing the use of the mother tongue as an introduction in learning Indonesian in elementary schools.